Identification of a Novel Hypovirulence-Inducing Hypovirus From Alternaria alternata - Li, Huan; Bian, Ruiling; Liu, Qian; Yang, Liu; Pang, Tianxing; Salaipeth, Lakha; Andika, Ida Bagus; Kondo, Hideki; Sun, Liying (Frontiers in Microbiology, 2019)
Mycoviruses are wide spread throughout almost all groups of fungi but only a small number of mycoviruses can attenuate the growth and virulence of their fungal hosts. Alternaria alternata is an ascomycete fungus that causes leaf spot diseases on various crop plants. In this study, we identified a novel ssRNA mycovirus infecting an A. alternata f. sp. mali strain isolated from an apple orchard in China. Sequence analyses revealed that this virus is related to hypoviruses, in particular to Wuhan insect virus 14, an unclassified hypovirus identified from insect meta-transcriptomics, as well as other hypoviruses belonging to the genus Hypovirus, and therefore this virus is designed as Alternaria alternata hypovirus 1 (AaHV1). The genome of AaHV1 contains a single large open-reading frame encoding a putative polyprotein (∼479 kDa) with a cysteine proteinase-like and replication-associated domains. Curing AaHV1 from the fungal host strain indicated that the virus is responsible for the slow growth and reduced virulence of the host. AaHV1 defective RNA (D-RNA) with internal deletions emerging during fungal subcultures but the presence of D-RNA does not affect AaHV1 accumulation and pathogenicities. Moreover, AaHV1 could replicate and confer hypovirulence in Botryosphaeria dothidea, a fungal pathogen of apple white rot disease. This finding could facilitate better understanding of A. alternata pathogenicity and is relevant for development of biocontrol methods of fungal diseases.